Copysites: Persepsi Wisatawan Mengenai Reproduksi Simulakra di Petite France - Ivana Chrisnauli Zevania Rajagukguk (Pusat Studi Pariwisata Universitas Gadjah Mada, 2023)
This study discusses simulacra reproduction at copysites, Petite France in Gapyeong, South Korea. Simulacra means a copy of a non-existent reality. Petite France was chosen because it is the only theme park with a French countryside vibe and combines pop art from The Little Prince, a french famous literature. France, the country that is most romanticized by tourists, making Korean and foreign tourists both those who have been to France and those who have not been interested in visiting Petite France to see how South Korea visualizes France. The theoretical basis for simulacra in this study is based on the research of Gravari-Barbas (2019) and Fangnan (2017). The method used in this study was semi-structured interviews with fourteen Korean tourists and seven foreign tourists visiting Petite France. The results of the study show that tourists do not care about the historical origins and cultural authenticity of the attractions and architecture in Petite France. It is known that their reason for visiting is for fun, entertainment, and to get a unique and different yet familiar experience through their lives. Petite France as copysites is the result of simulacra because it doesn't really imitate a real place in France, but creates a new French village in Korea and unify The Little Prince literature to add tourist’s experiences.